Clinical and Microbiological Characteristics of Bacteremic Pneumonia Caused by Klebsiella pneumoniae - Chen, I-Ren; Lin, Shih-Neng; Wu, Xin-Ni; Chou, Sheng-Hua; Wang, Fu-Der; Lin, Yi-Tsung (Frontiers in Cellular and Infection Microbiology, 2022)
Klebsiella pneumoniae is a common pathogen of nosocomial pneumonia worldwide and community-acquired pneumonia (CAP) in Asia. Previous studies have shown that K. pneumoniae bacteremic CAP is associated with high mortality. We aimed to revisit K. pneumoniae bacteremic pneumonia in the current era and determine the risk factors associated with 28-day mortality. Between January 2014 and August 2020, adult patients with K. pneumoniae bacteremic pneumonia in a medical center in Taiwan were identified. Clinical and microbiological characteristics were compared between CAP and nosocomial pneumonia. Risk factors for 28-day mortality were analyzed using multivariate logistic regression. Among 150 patients with K. pneumoniae bacteremic pneumonia, 52 had CAP and 98 had nosocomial pneumonia. The 28-day mortality was 52% for all patients, 36.5% for CAP, and 60.2% for nosocomial pneumonia. Hypervirulent K. pneumoniae was more prevalent in CAP (61.5%) than in nosocomial pneumonia (16.3%). Carbapenem-resistant K. pneumoniae was more prevalent in nosocomial pneumonia (58.2%) than in CAP (5.8%). Nosocomial pneumonia, a higher Severe Organ Failure Assessment score, and not receiving appropriate definitive therapy were independent risk factors for 28-day mortality. In conclusion, revisiting K. pneumoniae bacteremic pneumonia in the current era showed a high mortality rate. Host factors, disease severity, and timely effective therapy affect the treatment outcomes of these patients.